Analisis Efisiensi dan Produktivitas Pengelolaan Dana Wakaf di Indonesia: Pendekatan Data Envelopment Analysis (DEA) dan Malmquist Productivity Index (MPI) - Hanifa, Hanan; Eko Pramono, Sigid (Universitas Batanghari Jambi, 2025)
This research aims to analyze the performance of waqf management at zakat institutions in Indonesia by measuring their efficiency and productivity. This research was conducted for 5 (five) years using the Data Envelopment Analysis (DEA) and Malmquist Productivity Index (MPI) approaches. This research data includes registered zakat institutions in Indonesia that manage waqf funds. The research results show that the efficiency and productivity of waqf management in Indonesia has fluctuated, with a significant decline occurring during the Covid-19 pandemic in 2019 - 2021. The variable amount of waqf revenue is the main source of inefficiency, while technological changes are the main factor influencing waqf productivity. The results of the potential increase calculation show that the waqf revenue variable needs to be encouraged and increased.